(untitled) (Scientific journal of the Fergana State University, 2024)
Relevance of studying psychological health. The concept of “health” is syncretic, that is, it is characterized by complexity, ambiguity and dissimilarity. The history of the formation of psychological health as an autonomous, integral system of the psyche and personality, mainly due to abnormal manifestations, became the subject of scientific research, the textbook “Mental Health and Personal Protection Mechanisms” by L.D. Demina, I.A. Ralnikova. , specific mental health disorders of S. Freud, that the problem of social arousal was the first to be emphasized, A. Maslow’s ideas that mental health disorders in humanistic psychology are the result of the socialization of the individual, that “human psychological health” is not associated with individual mental processes and mechanisms, but belongs to the opinion of I.V. Dubrovina that A. Adler identified the seriousness of social interest as one of the criteria for assessing human health and showed it as a reference barometer, N.D. Lakosin and G.K. Ushakov’s following criterion of human health, including physical, distinguishing the criteria of the psychological and social level, the proposal of O.S. Vasiliev and F.R. Filatov that the term “personal mental health” is understood as a holistic personality, and not individual mental processes and mechanisms, psychological health of V.A. Labunskaya. - this is “the inner world of a person and various aspects. It is described in the article as “one of the inseparable features associated with relationships.”